Organophosphate esters in surface soils from a heavily urbanized region of Eastern China: Occurrence, distribution, and ecological risk assessment. (15th December 2021) - Tang, Jianfeng; Sun, Jing; Ke, Ziyan; Yin, Hongling; Yang, Lei; Yen, Haw; Li, Xinhu; Xu, Yaoyang
Abstract: Organophosphate esters (OPEs) pose increasing concerns for their widespread distribution in soil environments and potential threat to human health. In this study, we investigated the occurrence and associated risks of seven OPEs in surface soils and the potential influence of human activities on soil OPE contamination in a heavily urbanized region of the Yangtze River Delta in Eastern China. All target OPEs were detected in the soil samples (100% of samples) reflecting their widespread distribution in the study region. The total OPE concentration (the sum of the seven OPEs) ranged from 162.7 to 986.0 ng/g on a dry weight basis, with a mean value of 469.3 ± 178.6 ng/g. Tris (2-butoxyethyl) phosphate was the main compound, accounting for 67–78% of the total OPE concentration. Ecological risk assessment showed that tris(2-chloroisopropyl) phosphate, tris(2, 3-dichloropropyl) phosphate, tris(2-butoxyethyl) phosphate, and tris(2-ethylhexyl) phosphate posed a medium potential risk to terrestrial biota (0.1 < risk quotient <1). The human exposure estimation showed insignificant risks to local population. Redundancy analysis revealed that the individual and total OPE contaminations were positively correlated with human activity parameters. The total OPE concentrations were positively correlated to population density (R 2  = 0.38, P < 0.001), and urban land use percentage (R 2  = 0.39, P < 0.001), while negatively correlated to forest land use percentage (R 2  = 0.59, P < 0.001), suggesting a significant contribution of human disturbance to OPE pollution. These results can facilitate OPE contamination control and promote sustainable soil management in urbanized and industrialized regions. Highlights: Higher organophosphate ester (OPE) concentrations were observed in urban land. Tris (2-butoxyethyl) phosphate was the predominant OPE in surface soils. Soil OPE concentrations were positively correlated with human activity parameters. Urban land and population density played a key role in the OPE distribution.